1987
DOI: 10.1128/mcb.7.10.3503
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptionally inactive oocyte-type 5S RNA genes of Xenopus laevis are complexed with TFIIIA in vitro.

Abstract: An extract from whole oocytes of Xenopus laevis was shown to transcribe somatic-type 5S RNA genes -100-fold more efficiently than oocyte-type 5S RNA genes. This preference was at least 10-fold greater than the preference seen upon microinjection of 5S RNA genes into oocyte nuclei or upon in vitro transcription in an oocyte nuclear extract. The -100-fold transcriptional bias in favor of the somatic-type 5S RNA genes observed in vitro in the whole oocyte extract was similar to the transcriptional bias observed i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

9
46
1

Year Published

1988
1988
1992
1992

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(56 citation statements)
references
References 34 publications
9
46
1
Order By: Relevance
“…However, everything else does not appear to be equal, for in a transcription system derived from mature oocytes, the oocyte 5S RNA genes are transcribed in vitro at only a few percent of the rate of the somatic genes. These results confirm similar results recently reported by Peck et al (1987) and by Millstein et al (1987).…”
supporting
confidence: 83%
“…However, everything else does not appear to be equal, for in a transcription system derived from mature oocytes, the oocyte 5S RNA genes are transcribed in vitro at only a few percent of the rate of the somatic genes. These results confirm similar results recently reported by Peck et al (1987) and by Millstein et al (1987).…”
supporting
confidence: 83%
“…The so matic-type gene preference observed in oocyte extracts does not depend on levels of TFIIIA either, because suffi cient quantities of this protein are available to bind both active somatic-type and inactive oocyte-type genes Peck et al 1987). We examined several different types of extracts prepared from Xenopus oocytes, eggs, and embryos for their relative ability to transcribe the oocyte-and somatic-type 58 genes (Mill-Stein et al 1987;Peck et al 1987). We found two general classes of extracts: those that give approximately equiv alent levels of transcripts from the two genes (in inde pendent reactions), and those that preferentially support somatic-type transcription.…”
mentioning
confidence: 99%
“…Two explanations for preferential transcription of the somatic-type genes in the mature oocyte S-150 might be that these extracts are deficient in some component spe cifically required for oocyte-type transcription or that these extracts may contain a specific repressor of oo cyte-type transcription (Peck et al 1987). In this regard, Millstein et al (1987) have shown that stable inactive complexes are formed on the oocyte-type genes in S-150 extracts and that these complexes are refractory to acti vation after microinjection into living oocyte nuclei; however, Wolffe (1988) has shown that the addition of a crude protein fraction containing TFIIIC and other pro teins to S-150 extracts can elevate oocyte-type transcrip tion.…”
mentioning
confidence: 99%
See 2 more Smart Citations